(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The usefulness of colour Doppler sonography in hypo- or hyperthyroidism has been the subject of ongoing controversy for some time, with no clear findings coming from any of the current investigations. Goals: We want to learn more about thyroid Doppler sonographic findings in individuals who have an aberrant thyroid hormone status. Method: Coronal cross-sectional analysis. The study’s methodology involved recruiting 38 people with aberrant thyroid hormone states, including 21 hypothyroid and 17 hyperthyroid individuals. Not to mention the 15 healthy individuals who served as a control group. Every patient and volunteer underwent a thyroid Doppler examination, during which the researchers measured the thyroid hormone status by correlating the diffuse parenchymal vascularity patterns (DPVP) with the thyroid Doppler indices [peak systolic velocity (PSV), resistive index (RI), and pulsatility index (PI)]. End result: Both hyper- and hypo-thyroid hormone statuses were associated with an enhanced blood flow, as shown below: in the hypothyroid group, seven out of twenty-one patients (or 33.3% of the total) exhibited a diffuse hypervascular pattern (grades III and IV), while in the hyperthyroid group, sixteen out of twenty-one patients (or 76.1% of the total) had a high peak systolic velocity (>25 cm/s). A total of 14 patients (82.3%) exhibited significant PSV, while 5 patients (29.4%) exhibited DPVP (grade III & IV). Doppler findings that are out of the ordinary for the thyroid, such as high DPVP and/or PSV, are an extremely sensitive and specific predictor of an aberrant thyroid hormonal status (84.2%). In cases of hyper- or hypothyroid hormonal status, the sensitivity and specificity are almost identical. There was no statistically significant association between the individual thyroid hormones and high PSV; however, there was a correlation between high PSV and aberrant thyroid hormonal status (hypo- or hyperthyroid). While high DPVP was able to detect an abnormal thyroid hormone status with a 100% specificity rate, it had a low sensitivity rate of 29% and no statistically significant link with the abnormality. Neither the resistive index (RI) nor the pulsatility index (PI) was associated with hypo- or hyperthyroidism or abnormal thyroid hormone levels. In conclusion, elevated DPVP and PSV on thyroid Doppler are indicative of an aberrant thyroid hormone level but do not differentiate between hypo- and hyperthyroidism; furthermore, there was no statistically significant link between RI and PI and an abnormal thyroid hormonal status.